Linguistic landscape : a new approach to multilingualism - Gorter, D. (Durk) (Multilingual Matters, 2006)
Contains a collection of studies of the linguistic landscape - the use of written language on signs in the public sphere - in 5 different societies: Israel, Japan, Thailand, the Netherlands (Friesland) and Spain (Basque Country). This book focuses on multilingualism in the social context of the major cities.